Young people's strategies for navigating education, employment, and housing: a case study from Corby UK - Barke, Jenny; Boelman, Victoria; Khairunnisa, Vinkha; Shah, Salma (Frontiers in Sustainable Cities, 2023)
Introduction This paper reports the findings of research activity carried out as part of the UPLIFT project in Corby, United Kingdom. The project aimed to understand young people's experiences of education, employment and housing, and determine how young people navigate these domains, make choices and develop strategies within what is available to them. Through understanding the opportunities and strategies that young people employ across these domains, our aim was to consider how young people might engage locally to co-create a reflexive policy agenda. Methods We worked with peer researchers in Corby and interviewed local people (n = 40) and policy makers (n = 7) about the local context in Corby, and analyzed data, exploring themes. Results Findings highlighted the importance of young people understanding how systems work locally and suggest that young people, and their families, need greater support understanding how they can engage with and change systems. Discussion There needs to be better, easily accessible guidance developed around the support and opportunities that are available locally. Our research underlines the need to engage with young people in policy making to develop effective robust policy that works in a real-world context.